Photosynthetic Performance of Glyphosate Resistant and Glyphosate Susceptible Hairy Fleabane under Light Intensity - SILVA,D.R.O. (2017)
ABSTRACT: Herbicide resistance can confer lower competitive abilities; however scarse information is available about the photosynthetic performance between glyphosate-resistant and -susceptible hairy fleabane biotypes coming from areas with similar weed management history. Thus, the goal was to evaluate the photosynthetic performance under different light intensities between glyphosate-resistant and -susceptible hairy fleabane biotypes, from RR soybean fields with a similar weed management history. The tested factors were glyphosate resistant and susceptible biotypes and 12 levels of photosynthetic photon flux density. Plants were cultivated in plastic cups, and at the stage of 10-12 leaves they were subjected to treatments with artificial lighting systems. The net photosynthetic rate, stomatal conductance, substomatal CO2 concentration, transpiration rate, instantaneous water use efficiency, light compensation point and quantum yield were evaluated. In all the evaluated photosynthetic parameters, biotype R showed superior characteristics compared to susceptible biotypes, with the exception of the transpiration rate, where there were no differences. The differences between biotypes may not be associated to glyphosate resistance or susceptibility, but to the evolutionary characteristics of the biotypes.